Effects of Ramadan and Non-ramadan Intermittent Fasting on Gut Microbiome - Mousavi, Seyedeh Neda; Rayyani, Elham; Heshmati, Javad; Tavasolian, Ronia; Rahimlou, Mehran (Frontiers in Nutrition, 2022)
Background: In recent years, intermittent fasting has gained popularity in the health and wellness in the world. There are numerous types of intermittent fasting (IF), all of which involve fasting periods that last longer than an overnight fast and involve limited meal time-windows, with or without calorie restriction. The objective of this review is to summarize the current evidence for the effects of Ramadan and non-Ramadan intermittent fasting on gut microbiome. Methods: We explored Pubmed, Scopus, Web of Science and Google Scholar according to the PRISMA criteria (Preferred Reporting Items for Systematic reviews and Meta-Analysis). Animal and human studies were screened and reviewed separately by two researchers. Results: Twenty-eight studies were selected after screening. Some of the studies were performed on animal models and some on humans. The results of these studies showed different evidence of the effect of fasting diets on the gut microbiota such as increasing microbial diversity, reducing inflammation, and increasing the production of beneficial microbial compounds known as short chain fatty acids (SCFAs). Many beneficial bacteria, such as Lactobacillus and Bifidobacterium, had significant shifts in individuals on fasting diets. However, some studies have reported adverse effects of fasting diets on the structure of the microbiome. Conclusion: In general, most studies have seen favorable results following adherence from the fasting diets on the intestinal microbiome. However, because more studies have been done on animal models, more human studies are needed to prove the results.